Confidence via correction: The effect of judgment correction on consumer confidence - Francine Espinoza Petersen; Rebecca W. Hamilton (European School of Management and Technology (ESMT), 2013)
At times, consumers are motivated to reduce the influence of a product recommendation on their judgments. Based on previous research, it is unclear whether this correction process will increase or decrease consumers' confidence in their judgments. We find that source credibility moderates the effect of correction on confidence: correction decreases confidence when a product recommendation comes from a high credibility source but increases confidence when the same message comes from a low credibility source. As a result, correction increases the effectiveness of recommendations from low credibility sources on purchase intentions. Notably, this confidence via correction effect is further moderated by elaboration, such that the effect is attenuated for high elaboration consumers. Our results have implications for understanding consumers' reactions to persuasive messages and for both marketing practitioners and consumer protection agencies using correction cues to influence message persuasiveness.
urn:nbn:de:101:1-201307224110
Keywords: 650; Confidence; correction; credibility; persuasion; advertising